2006
DOI: 10.1242/jeb.02057
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and behavioural changes during water absorption in toads, Bufo alvarius and Bufo marinus

Abstract: SUMMARY Blood cell flux (BCF) in the pelvic skin of Bufo marinus was lower than Bufo alvarius when toads rehydrated from deionised water (DI) or 50 mmol l–1 NaCl (NaCl). Despite the lower BCF in B. marinus, water absorption was not different between the species when toads rehydrated from DI or NaCl. When fluid contact was limited to the pelvic skin, water uptake from NaCl was lower than from DI, but became greater than uptake from DI as the immersion level increased. Hydrophobic beeswax coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…Cloudsley-Thompson, 1967;Claussen, 1969;Tracy, 1976). Although uncertain, we suspect that some of the physiological parameters affecting skin permeability respond differently to combined changes in temperature and hydration state, possibly involving adjustments in local microcirculatory perfusion of the pelvic patch (Slivkoff and Warburton, 2001;Viborg and Rosenkilde, 2004;Viborg et al, 2006) and constitutive changes in this region's water permeability (Willumsen et al, 2007), mediated by changes in the expression of aquaporins (Hasegawa et al, 2003;Suzuki et al, 2007;Saitoh et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Cloudsley-Thompson, 1967;Claussen, 1969;Tracy, 1976). Although uncertain, we suspect that some of the physiological parameters affecting skin permeability respond differently to combined changes in temperature and hydration state, possibly involving adjustments in local microcirculatory perfusion of the pelvic patch (Slivkoff and Warburton, 2001;Viborg and Rosenkilde, 2004;Viborg et al, 2006) and constitutive changes in this region's water permeability (Willumsen et al, 2007), mediated by changes in the expression of aquaporins (Hasegawa et al, 2003;Suzuki et al, 2007;Saitoh et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…7a). Viborg et al. (2006) similarly showed that cutaneous blood flow in hydrated Bufo alvarius could be stimulated to levels comparable to dehydration when toads with an empty bladder were given access to water (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The degree of stimulation of blood flow is similar to that of mild dehydration. Source: from Viborg et al. (2006).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they absorb water across a specialized patch of pelvic skin-the seat patch-and alter circulatory patterns and posture to regulate water uptake (Burggren and Vitalis 2005;Viborg et al 2006).…”
Section: Systems Physiologymentioning
confidence: 99%